2017
DOI: 10.21037/tau.2017.04.36
|View full text |Cite
|
Sign up to set email alerts
|

The role of PET/CT imaging in penile cancer

Abstract: Positron emission tomography (PET) imaging with 18F-fluorodeoxyglucose (FDG) combined with computed tomography (CT) provides functional imaging combined with anatomic information, improving diagnostic accuracy and confidence. Although virtually all primary penile tumors are FDG-avid, PET/CT is not recommended for primary tumor staging as it has limited spatial resolution and is hampered by urinary FDG excretion. The accuracy of PET/CT for lymph node staging seems to improve with the pretest likelihood of metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…41 Limited molecular or imaging biomarkers have been evaluated or determined to be useful for early assessment of the benefit of neoadjuvant chemotherapy, and scarce data are available regarding the possible role of [ 18 F]-FDGePET for assessing interim response to neoadjuvant therapy. 52,53 Among the largest trials that have established the approach of neoadjuvant chemotherapy followed by surgical treatment as the standard of care is a prospective singlecenter nonrandomized phase 2 clinical trial by Pagliaro et al 41 This study's objective was determining the response rate, time to progression (TTP), and overall survival (OS) of patients with bulky adenopathy who were receiving neoadjuvant chemotherapy in the following combination: paclitaxel (175 mg/m 2 administered over 3 hours on day 1), ifosfamide (1200 mg/m 2 on days 1 to 3), and cisplatin (25 mg/m 2 on days 1 to 3 every 3 weeks) (TIP), with the goal of completing a total of 4 cycles before proceeding with consolidation surgical treatment. Thirty men received chemotherapy, and 23 patients (76.7%) completed the planned 4 courses of chemotherapy.…”
Section: Role Of Neoadjuvant Chemotherapy Inmentioning
confidence: 99%
“…41 Limited molecular or imaging biomarkers have been evaluated or determined to be useful for early assessment of the benefit of neoadjuvant chemotherapy, and scarce data are available regarding the possible role of [ 18 F]-FDGePET for assessing interim response to neoadjuvant therapy. 52,53 Among the largest trials that have established the approach of neoadjuvant chemotherapy followed by surgical treatment as the standard of care is a prospective singlecenter nonrandomized phase 2 clinical trial by Pagliaro et al 41 This study's objective was determining the response rate, time to progression (TTP), and overall survival (OS) of patients with bulky adenopathy who were receiving neoadjuvant chemotherapy in the following combination: paclitaxel (175 mg/m 2 administered over 3 hours on day 1), ifosfamide (1200 mg/m 2 on days 1 to 3), and cisplatin (25 mg/m 2 on days 1 to 3 every 3 weeks) (TIP), with the goal of completing a total of 4 cycles before proceeding with consolidation surgical treatment. Thirty men received chemotherapy, and 23 patients (76.7%) completed the planned 4 courses of chemotherapy.…”
Section: Role Of Neoadjuvant Chemotherapy Inmentioning
confidence: 99%
“…In a limited study with seven men (stage T1b-T2), this detection method showed sensitivity of 100%, specificity of 97%, positive predictive value of 81.2%, and negative predictive value of 100% (15,16). This provides promise as PET/CT is only 57% accurate in predicting ILNM in patients with normal groin exams compared to 96% in patients with palpable nodes (17). Conventional imaging modalities rely on size criteria (>8-10mm) to diagnose ILNM.…”
Section: Clinical/pathological Factorsmentioning
confidence: 99%
“…The carcinoma penis is one of the predisposing factors caused by HPV (human papilloma virus) [ 24 , 25 ].…”
Section: Viral Infections In Abdomenmentioning
confidence: 99%